Internet censorship detected in Jordan (Jordan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Jordan. Data sourced from CensoredPlanet.
Censorship Incident ID: JO-2026-0044. Severity: critical. Confidence: 65%